Эсхатология святителя Викторина Петавийского: богословско-филологический анализ латинских терминов (Eschatologia św. Wiktoryna z Petawium. Teologiczno-filozoficzna analiza terminów łacińskich) - Chandoga, Nikołaj Anatoliewicz (Vox Patrum, 2018)
Eschatology of Victorinus of Poetovio as one of the ante-nicene chiliasts is closely related to the eight-day, or eight-thousand concept of the history of the world and the human race. According to this concept, the universe will exist four periods: the first – from the creation of God the world and the first people before the first coming of Christ on the earth (the first five days of creation, or the first five thousand years); the second – from the first coming of Christ to the second coming of Christ (the sixth day of creation, or the sixth thousand years); the third – from the second coming of Christ and to the beginning of the Last Judgment (the seventh day of rest, or the seventh thousand years); the fourth – from the beginning of the Last Judgment and to infinity (the eighth day of Judgment and eternal rest, or eight thousand years). An important aspect of the eschatology of Victorinus prelate is its christological and soteriological aspects, that is, the Lord Jesus Christ takes part in human history in each of these eight millennia. In other words, the Savior not only created the world and the first people, but daily takes care of the crown of his creation – the human race. This can be traced in the disclosure of the theological terminology of the end of Victorinus of Poetovio.